Alcohol use disorder: An analysis of the evidence underpinning clinical practice guidelines. (1st March 2022) - Tanner, David; Minley, Kirstien; Snider, Kelsey; Hartwell, Micah; Torgerson, Trevor; Ottwell, Ryan; Beaman, Jason; Vassar, Matt
Abstract: Background: As Clinical Practice Guidelines (CPGs) provide effective guidance for providing medical care for individuals with alcohol use disorder (AUD), the evidence behind them should be robust. Objective: Our primary objective was to critically appraise the methodological and reporting quality of systematic reviews cited within CPGs regarding the treatment of AUD. Our secondary objective was to determine how frequently Cochrane Reviews were cited as justification and to evaluate appraisals between Cochrane and non-Cochrane reviews. Methods: We searched PubMed to identify CPGs for the treatment of AUD published between 2015 and 2021. Systematic reviews included in each CPG were evaluated using the Preferred Reporting Instrument for Systematic Reviews and Meta-Analyses (PRISMA) and a validated quality assessment tool (AMSTAR-2). Additional study characteristics were recorded. Results: From the screening process, 98 systematic reviews from 6 CPGs met inclusion criteria. PRISMA adherence ranged from 72% to 85% (mean of 79%). AMSTAR-2 adherence ranged from 52% to 73% (mean of 68%). AMSTAR appraisal ratings found 32 (35.6%) critically low, 10 (11.1%) low, 35 (38.9%) moderate, and only 13 (14.4%) high systematic reviews. Cochrane systematic reviews displayed greater PRISMA (0.92 vs. 0.75: p < 0.001) and AMSTAR-2 (0.90 vs. 0.61.; p < 0.001) scores compared to the non-Cochrane studies. Conclusion: Systematic reviews included in CPGs for AUD treatment showed variable adherence to PRISMA and AMSTAR-2 guidelines, with almost half of the systematic reviews being critically low to low methodological quality. Given the prevalence of alcohol use disorder, methodological and reporting quality recommendations are important to strengthening evidence informing CPGs. Highlights: Methodologic quality of systematic reviews on Alcohol Use Disorder varied. Only 12% of systematic reviews reported the funding source of included studies. Critically appraising systematic reviews in clinical practice guidelines is important. Risk of bias assessment of individual studies was poorly reported.